Environmental Management Systems, Firm Size, and Corporate Governance as Determinants of Carbon Emission Disclosure - Ayushabrina, Fina; Sunarsih, Uun (Research of Accounting and Governance, 2026)
This study examines the effects of Environmental Management System (EMS), firm size, institutional ownership, and the audit committee on carbon emission disclosure among energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative associative approach, secondary data from 33 firms selected through purposive sampling are analyzed, yielding 132 firm-year observations. Carbon emission disclosure is measured using a disclosure index; EMS is proxied by ISO 14001 certification; firm size by the natural logarithm of total assets; institutional ownership by the proportion of institutional shareholding; and the audit committee by the frequency of audit committee meetings. Panel data regression is conducted using EViews, with the fixed-effects model chosen based on model selection tests. The results indicate that EMS has a significant positive effect on carbon emission disclosure, suggesting greater transparency among firms with structured environmental management systems. Firm size also positively influences disclosure, reflecting higher public visibility and accountability. Institutional ownership significantly enhances disclosure through effective monitoring, while audit committee activity strengthens disclosure practices via improved oversight and governance. Overall, the findings highlight the importance of environmental management and corporate governance in improving sustainability reporting and supporting Indonesia’s transition toward a low-carbon economy.